A metal-binding member of the late embryogenesis abundant protein family transports iron in the phloem of Ricinus communis L. - Krüger, Claudia; Hell, Rüdiger (The journal of biological chemistry, 2002)
The transport of metal micronutrients to developing organs in a plant is mediated primarily by the sieve elements. Ligands are thought to form complexes with the free ions in order to prevent cellular damage, but no binding partners have been unequivocally identified from plants so far. This study has used the phloem-mediated transport of micronutrients during the germination of the castor bean seedling to identify an iron transport protein (ITP). It is demonstrated that essentially all 55Fe fed to seedlings is associated with the protein fraction of phloem exudate. It is shown that ITP carries iron in vivo and binds additional iron in vitro. ITP was purified to homogeneity from minute amounts of phloem exudate using immobilized metal ion affinity chromatography. It preferentially binds to Fe3+ but not to Fe2+ and also complexes Cu2+, Zn2+, and Mn2+ in vitro. The corresponding cDNA of ITP was cloned using internal peptide fragments. The deduced protein of 96 amino acids shows high similarity to the stress-related family of late embryogenesis abundant proteins. Its predicted characteristics and its RNA expression pattern are consistent with a function in metal ion binding. The ITP from Ricinus provides the first identified micronutrient binding partner for phloem-mediated long distance transport in plants and is the first member of the late embryogenesis abundant protein family shown to have such a function.